Antioxidant Activity Test of Peel-off Mask of Ethanol Extract of Kitolod Leaves (Isotoma Longiflora L) - Nur Indah Sari; Angga Bayu Budiyanto; Ratih Arum Astuti (Jurnal EduHealth, 2025)
Free radicals are one of the main causes of skin cell damage, resulting in premature aging. Antioxidants play an important role in neutralizing free radicals, thereby maintaining skin health. Kitolod leaves (Isotoma longiflora L.) are known to contain flavonoids, alkaloids, saponins, and polyphenols that have antioxidant potential. This study aims to formulate 70% ethanol extract of kitolod leaves into a peel-off gel mask preparation and evaluate its physical stability and antioxidant activity. The research method is experimental with variations in extract concentration of 5%, 10%, and 15%. Physical evaluation of the formulation included organoleptic testing, homogeneity, pH, viscosity, spreadability, adhesion, and drying time, while antioxidant activity was tested using the DPPH method. The results showed that all formulations met the characteristics of a good peel-off mask preparation and remained stable for 14 days of storage. The antioxidant activity test using the method showed that the IC50 value of kitolod leaf extract was 52.84 ppm, which is classified as strong. Thus, the peel-off gel mask containing kitolod leaf extract has the potential to be developed as a natural cosmetic product with good antioxidant activity.